Harnessing lactic acid bacteria for nicotinamide mononucleotide biosynthesis: a review of strategies and future directions - Kong, Linghui; Li, Xinyu; Liu, Taiyu; Yao, Qingshou; Qin, Jiayang (Frontiers in Microbiology, 2024)
Nicotinamide mononucleotide (NMN), one of the crucial precursors of nicotinamide adenine dinucleotide, has garnered considerable interest for its pharmacological and anti-aging effects, conferring potential health and economic benefits for humans. Lactic acid bacteria (LAB) are one of the most important probiotics, which is commonly used in the dairy industry. Due to its probiotic properties, it presents an attractive platform for food-grade NMN production. LAB have also been extensively utilized to enhance the functional properties of pharmaceuticals and cosmetics, making them promising candidates for large-scale up synthesis of NMN. This review provides an in-depth analysis of various metabolic engineering strategies, including enzyme optimization, pathway rewiring, and fermentation process enhancements, to increase NMN yields in LAB. It explores both CRISPR/Cas9 and traditional methods to manipulate key biosynthetic pathways. In particular, this study discussed future research directions, emphasizing the application of synthetic biology, systems biology, and AI-driven optimization to further enhance NMN production. It provides invaluable insights into developing scalable and industrially relevant processes for NMN production to meet the growing market demand.